Social deprivation in Scottish populations with pulmonary hypertension secondary to connective tissue disease and chronic thromboembolic disease. Issue 4 (10th November 2020) - McGettrick, Michael; McCaughey, Paul; MacLellan, Alexander; Brewis, Melanie; Church, A. Colin; Johnson, Martin K.
Socioeconomic factors have been shown to have an adverse impact on survival in some respiratory diseases. Studies from the USA and China have suggested worse survival in idiopathic pulmonary arterial hypertension in low socioeconomic groups. We looked at the effect of deprivation on the outcomes in patients with connective tissue disease-associated pulmonary hypertension (CTDPH) and chronic thromboembolic pulmonary hypertension (CTEPH) in a retrospective observational study. Data were obtained from 232 patients with CTDPH and 263 with CTEPH who were under the care of the Scottish Pulmonary Vascular Unit, Glasgow, UK. We used Cox proportional hazards regression to assess for a relationship between deprivation and survival. We found no difference in survival across deprivation quintiles in the CTDPH (p=0.26) or CTEPH cohorts (p=0.18). We constructed multivariate models using enrolment time, age, sex and body mass index, with no significant change in findings. There was no difference between expected and observed population distribution of CTDPH (p=0.98) and CTEPH (p=0.36). Whilst there was no difference in presenting functional class in the CTDPH group, the CTEPH patients in more deprived quintiles presented in a worse functional class (p=0.032). There was no difference between quintiles of CTEPH patients who had distal or proximal disease (p=0.75), or who underwent surgery (p=0.5). Increased social deprivation is not associated with worse survival in patients with CTDPH and CTEPH managed in the Scottish National Health Service. Whilst there is no evidence of referral barriers in CTDPH, this may not be the case in CTEPH, as lower deprivation was associated with worse functional class at presentation. Increased social deprivation is not associated with worse survival in patients with connective tissue disease-associated pulmonary hypertension or chronic thromboembolic pulmonary hypertension managed in the Scottish NHS https://bit.ly/32KbzSv